2022
DOI: 10.1093/neuonc/noac071
|View full text |Cite
|
Sign up to set email alerts
|

Blood exosomes-based targeted delivery of cPLA2 siRNA and metformin to modulate glioblastoma energy metabolism for tailoring personalized therapy

Abstract: Background Targeting GBM energy metabolism through multiple metabolic pathways has emerged as an effective therapeutic approach. Dual inhibition of phospholipid and mitochondrial metabolism with cytoplasmic phospholipase A2 (cPLA2) knockdown and metformin treatment could be a potential strategy. However, the strategic prerequisite is to explore a carrier capable of co-delivering the therapeutic combination to cross the blood-brain barrier (BBB) and preferentially accumulate at the GBM site. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 29 publications
0
23
0
Order By: Relevance
“…To solve these problems, Zhan et al used biological system-derived exosomes (Exos) to load sicPLA2 and metformin, yielding Exo-Met/sicPLA2 for GBM therapy. 155 A typical "saucer-like" nanomorphology was found for both the empty Exos and Exo-Met/sicPLA2, with diameters of 116.5 ± 3.2 nm and 128.1 ± 7.7 nm, respectively. It was found that PTRF expression was significantly increased in the GBMs.…”
Section: Combinatory Therapeutic Drugs For Gbm Treatmentmentioning
confidence: 92%
“…To solve these problems, Zhan et al used biological system-derived exosomes (Exos) to load sicPLA2 and metformin, yielding Exo-Met/sicPLA2 for GBM therapy. 155 A typical "saucer-like" nanomorphology was found for both the empty Exos and Exo-Met/sicPLA2, with diameters of 116.5 ± 3.2 nm and 128.1 ± 7.7 nm, respectively. It was found that PTRF expression was significantly increased in the GBMs.…”
Section: Combinatory Therapeutic Drugs For Gbm Treatmentmentioning
confidence: 92%
“…Although there are currently no engineered exosomes to directly target various metabolic pathways in the TME, exosomes can be combined with classical drugs or modalities as an adjuvant therapy to improve the efficacy of anti-tumor therapy. It has been shown that combination of exosome-mediated cPLA2 siRNA and metformin reduces the growth of glioblastoma xenografts by impairing the energy metabolism of mitochondria [295]. Photodynamic therapy (PDT) is a novel method of treating tumors with photosensitizing drugs and laser activation [300].…”
Section: Exosome-based Tumor Metabolic Therapiesmentioning
confidence: 99%
“…Understanding of the impact of ribonucleic acids in both normal and disease states is continuing to rapidly expand. While understanding of microRNA 1a,2a and short-interfering RNAs 3a,4a continues to emerge, lncRNA molecules are an exciting new focus for cancer researchers, including those who study GBM. The translation of lncRNA biological knowledge into putative therapeutics has not yet been realized because of the novelty of understanding and because of the diverse roles they play in GBM tumorigenesis.…”
Section: Commentsmentioning
confidence: 99%